Public perceptions of brain health: an international, online cross-sectional survey - Budin-Ljøsne, I; Mowinckel, AM; Bodorkos Friedman, B; Ebmeier, KP; Drevon, CA; Bruu Carver, R; Zsoldos, E; Fredheim, NAG; Sørensen, Ø; Baaré, WFC; Skak Madsen, K; Fjell, AM; et al. (BMJ Publishing Group, 2022)
Objectives: To investigate public perspectives on brain health. Design: Cross-sectional multi-language online survey. Setting: Lifebrain posted the survey on its website and social media and shared it with stakeholders. The survey was open from June 4, 2019 until August 31, 2020. Participants: N=27,590 aged ≥18 years from 81 countries in five continents completed the survey. The respondents were predominantly women (71%), middle-aged (41-60 years; 37%) or above (>60 years; 46%), highly educated (69%) and resided in Europe (98%). Main outcome measures: Respondents’ views were assessed regarding factors that may influence brain health, life periods considered important to look after the brain, and diseases and disorders associated with the brain. We run exploratory linear models at a 99% level of significance to assess correlates of the outcome variables, adjusting for likely confounders in a targeted fashion. Results: Of all significant effects, the respondents recognized the impact of lifestyle factors on brain health but had relatively less awareness of the role socio-economic factors might play. Most respondents rated all life periods as important for the brain (95-96%), although the prenatal period was ranked significantly lower (84%). Equally, women and highly educated respondents more often rated factors and life periods to be important for brain health. Ninety-nine percent of respondents associated Alzheimer’s disease and dementia with the brain. The respondents made a connection between mental health and the brain, and mental disorders such as schizophrenia and depression were significantly more often considered to be associated with the brain than neurological disorders such as stroke and Parkinson’s disease. Few respondents (<32%) associated cancer, hypertension, diabetes, and arthritis with the brain. Conclusions: Differences in perceptions of brain health were noted among specific segments of the population. Policies providing information about brain-friendly health behaviours and targeting people less likely to have relevant experience may be needed.